PELAKSANAAN PROGRAM PERCEPATAN PENDAFTRAN TANAH SISTEMATIS LENGKAP (PTSL) DI KELURAHAN BATU LAYANG KECAMATAN PONTIANAK UTARA - NIM. A1012161045, TRI NOVIAN ANANDA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The Program Program to Accelerating the Implementation of Complete Systematic Land Registration (PTSL) Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 35 of 2016 in Sungai Jawi Village, Pontianak City District, The background to Complete Systematic Land Registration is in order to provide legal certainty and legal protection for people's land rights fairly and evenly, and to encourage economic growth in particular, it is necessary to accelerate complete systematic land registration throughout the Republic of Indonesia. Thus, it can encourage economic growth and improve people's welfare. Based on the Stipulation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration.Based on the description of the research background above, there are problems, namely (1) Why has the Program for accelerating the Implementation of Complete Systematic Land (PTSL) in Sungai Jawi Village, Pontianak City District not been implemented optimally in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration?In this study, the author uses an empirical method with descriptive analysis, so the author can draw several conclusions as follows (1) That with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL) has not been implemented optimally in accordance with the objectives and expectations of the Agrarian and Spatial Planning Office/National Land Agency (2) The implementation of Complete Systematic Land Registration (PTSL) in Batu Layang Village, North Pontianak District has not been implemented optimally because there are obstacles, namely the lack of support from the Village / Sub-district Government regarding the Land Rights and Filing, the Pontianak City Land Office has tried to write to the City Government for BPHTB relief, dividing and organizing the existing PTSL Officers into 4 teams, each of which is coordinated by a physical task force and a legal task force, conducting Land Clearing first to facilitate the measurement process on the land at the location, conducting socialization to the community and the village head so that they do not believe in irresponsible individuals outside the provisions, Communities whose domiciles are outside the village/sub-district where PTSL is located are still registered for land but no land certificates are issued, and is still trying to be able to notify Those concerned.Keywords: Implementation, Land Registration, Systematic Abstrak Program Percepatan Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) Berdasarkan Peratura Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 35 Tahun 2016 Di Kelurahan Sungai Jawi Kecamatan Pontianak Kota, Hal-hal yang melatarbelakangi tentang Pendaftaran Tanah Sistematis Lengkap adalah dalam rangka memberikan jaminan kepastian hukum dan perlindungan hukum hak atas tanah rakyat secara adil dan merata, serta mendorong pertumbuhan ekonomi rakyat khususnya, perlu dilakukan percepatan pendaftaran tanah sistematis lengkap di seluruh wilayah Republik Indonesia. Dengan demikian dapat mendorong pertumbuhan ekonomi dan meningkatkan kesejahteraan masyarakat.Berdasarkan Penetapan Peraturan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 6 Tahun 2018 tentang Pendaftaran Tanah Sistematis Lengkap.Berdasarkan uraian latar belakang penelitian diatas, terdapat permasalahan yaitu (1) Mengapa Program Percepatan Pelaksanaan Pendaftaran Tanah Sistematis Lengkap(PTSL) di Kelurahan Sungai Jawi, Kecamatan Pontianak Kota belum terlaksana secara optimal sesuai dengan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 6 Tahun 2018 tentang Pendaftaran Tanah Sistematis Lengkap ?Dalam Penelitian ini penulis menggunakan metode empiris dengan deskriptif analisis maka penulis dapat menarik beberapa kesimpulan sebagai berikut (1) Bahwa dengan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 6 Tahun 2018 tentang Pendaftaran Tanah Sistematis Lengkap (PTSL) belum terlaksana secara optimal sesuai dengan tujuan dan harapan Kantor Agraria dan Tata Ruang/Badan Pertanahan Nasional (2) Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kelurahan Batu Layang Kecamatan Pontianak Utara masih belum terlaksana secara optimal karena terdapat kendala-kendala yaitu seperti Kurangnya dukungan dari Pemerintah Desa / Kelurahan berkenaan dengan Alas Hak dan Pemberkasan, Kantor Pertanahan Kota Pontianak sudah berupaya menyurati pihak Pemerintah Kota untuk keringanan BPHTB, Membagi dan mengatur Petugas PTSL yang ada menjadi 4 tim yang masing-masing di koordinir oleh satgas fisik dan satgas yuridis, melakukan Land Clearing terlebih dahulu untuk mempermudah proses pengukuran di tanah lokasi terscbut, Melakukan sosialisasi kepada masyarakat dan lurah agar tidak percaya kepada oknum-oknum yang tidak bertanggung jawab di luar ketentuan, Masyarakat yang domisilinya diluar desa/kelurahan lokasi PTSL tetap dilakukan pendaftaran tanahnya namun tidak diterbitkan sertipikat tanah, serta tetap berupaya untuk dapat memberi tahu kepada yang bersangkutan.Kata Kunci: Pelaksanaan, Pendaftaran Tanah, Sistematis